The Effects of Artificial Intelligence and Design Thinking on Enhancing Organisational Performance in The Context of Digital Transformation - Nouria BENNAMA; Fatima Zahra BENNAMA; Adel BELKADI (Revista de Management Comparat International)
This study investigates the relationship between artificial intelligence (AI), design thinking, and business performance in the context of digital transformation. Method: A quantitative cross-sectional design was applied using data from 100 participants selected through convenience sampling. A validated questionnaire was used, distributed both online and in print. Reliability was confirmed via Cronbach’s Alpha. The PROCESS macro in SPSS was employed to test direct, indirect, and moderated effects. Results: Findings show that AI significantly enhances business processes through automation and improved decision-making. Design thinking plays a mediating role by aligning technology solutions with user needs. The interaction between AI and design thinking contributes to improved business performance, notably in revenue growth, customer satisfaction, and innovation. Discussion: The integration of AI and design thinking supports organizational transformation in digital contexts. These results offer insights for managers and researchers seeking to leverage technology and human-centered design to improve business outcomes